170 The Accuracy of Multimodality Intraoperative Neuromonitoring to Predict Postoperative Neurological Deficits Following Cervical Laminoplasty. (1st August 2016) - Burke, John Frederick; Ohya, Junichi; Vogel, Todd Douglas; Virk, Michael; Chou, Dean; Mummaneni, Praveen V.
Abstract: INTRODUCTION: The utility multimodality intraoperative neuromonitoring (IONM) to predict postoperative neural deficits following cervical laminoplasty remains unclear. The purpose of this study is to determine whether multimodality IONM can predict postoperative C5 palsy. METHODS: We retrospectively reviewed 131 consecutive patients with cervical myelopathy who underwent open door laminoplasty utilizing motor evoked potential (MEP) monitoring combined with somatosensory-evoked potentials (SSEP) and free-running electromyography (EMG). We reviewed abnormal findings in the IONM record including EMG, MEP, and SSEP changes documented as transient or persist at the end of surgery. RESULTS: Postoperative C5 palsy occurred in 3 patients (2.2%). Two were acute in onset and one occurred 4 days postoperatively. Significant MEP alerts occurred in 12 patients. Four patients had MEP intraoperative alerts in their deltoid or biceps, of which 2 alerts were transient and 2 alerts were persistent at the end of surgery. Significant intraoperative SSEP change was not observed in this study. For the prediction of postoperative acute-onset C5 palsy, MEP alerts in the deltoid or biceps had 100% sensitivity and 98.4% specificity. Transient or persistent MEP alerts in the deltoid or biceps have the same positive predictive value with sensitivity of 50.0% and specificity of 99.2%. CONCLUSION: The incidence of any neurological deficit including C5 palsy during laminoplasty while utilizing multimodality IONM was relatively low. MEP alerts in the deltoids or biceps had 100% sensitivity and 98.4% specificity to predict a postoperative acute C5 palsy.